Bore-Induced Local Scour around a Circular Structure - Lavictoire, Alexandra (Université d'Ottawa / University of Ottawa, 2015)
Recent natural disasters, such as major tsunamis, have prompted researchers and practicing engineers to improve their understanding of the impacts of bore-like waves on structures and their foundations. The high velocity and the relatively short duration of hydraulic bores causes local scouring which is different from that generated by river flows and waves. The present study uses an experimental model to simulate the propagation of a hydraulic bore over a movable sediment bed placed around a circular pier-like structure. Measurements of water surface elevation, bore propagation velocity and scour distribution were taken. The linear relationship between reservoir depth and bore depth led to an increase in flow acceleration, and thus to an increase in flow velocity. Final scour bed elevations indicated that scour depth was highly dependent on the bore velocity. The scour depth ratios suggested in current design guidelines were significantly lower than those obtained in this study.
Keywords: Hydraulic bore; Local scour; Tsunami scour; Circular Structure